Singapore Management University Report to Stakeholders 2006 - 2007 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2006)
SMU was founded to add diversity to higher education in Singapore, and to serve as a catalyst for change. Eight years on, the University continues to set new benchmarks for nurturing responsible leadership, developing diverse talents and spearheading research that has impact and real-world relevance. In the past academic year, SMU added a new school, graduate programmes and centres of excellence and forged new and deeper relationships with industry, academic and civic partners. These advances built on our existing strengths and moved us forward on a path of purposeful change and growth that reinforced our vision to be a premier university, internationally recognised for its excellence in research and teaching.